2021
DOI: 10.1186/s13662-021-03584-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing reservoir control in the co-dynamics of HIV-VL: from mathematical modeling perspective

Abstract: HIV patients are vulnerable to developing active visceral leishmaniasis (VL). To understand this complication, we studied a mathematical model for HIV and visceral leishmaniasis coinfection. In this approach, we reckoned two distinct equilibria: the disease-free and the endemic equilibria. The local and global stability of the disease-free equilibrium were thoroughly investigated. To further support the qualitative findings, we performed simulations to quantify the changes of the dynamical behavior of the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mathematical modeling plays a significant role in depicting how infectious diseases spread within a community [8]. It has been known that there was only one methicillin‐resistant Staphylococcus aureus (MRSA) strain that existed in hospital, called hospital‐acquired MRSA (HA‐MRSA), which predominantly infected elderly and debilitated patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling plays a significant role in depicting how infectious diseases spread within a community [8]. It has been known that there was only one methicillin‐resistant Staphylococcus aureus (MRSA) strain that existed in hospital, called hospital‐acquired MRSA (HA‐MRSA), which predominantly infected elderly and debilitated patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of the co-infection of these diseases must be initiated in a systemic manner because their drugs do not always work well together. While some co-infection mathematical models have been developed and analyzed to understand the transmission dynamics of various diseases [3, 29,30], such efforts for a mathematical model to understand the visceral leishmaniasis (VL) and tuberculosis (TB) co-infection have not taken place yet (to the best of our knowledge). Therefore, in this study, we develop and analyze a mathematical model designed to understand the dynamics of VL and TB co-infection.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the introduction of PrEP has a positive effect on the limitation of the spread of HIV. Melese and Alemneh [22] developed a transmission dynamics model for VL-HIV coinfection by splitting the population into ten compartments. From the result they achieved, the authors concluded that increasing the rate of visceral leishmaniasis (VL) recovery (ϕ 1 ), the recovery rate for VL-HIV Coinfection (ϕ 2 ), removing reservoirs (c 1 ), and minimizing the contact rate (β h ) are important in controlling the transmission of individual and coinfection disease of VL and HIV.…”
Section: Introductionmentioning
confidence: 99%